Seafloor gas seeps and sediment failures triggered by the August 17, 1999 earthquake in the Eastern part of the Gulf of Izmit, Sea of Marmara, NW Turkey - Kusçu, I; Okamura, M; Matsuoka, H; Gökasan, E; Awata, Y; Tur, H; Simsek, M; Keçer, M (ELSEVIER, 2005)
On August 17, 1999, a major earthquake (M-w=7.4) occur-red, affecting a large area in northwestern Turkey. A 150-km-long section of the North Anatolian Fault ruptured from the entrance of the Gulf of Izmit to Golyaka in the east during the earthquake. We utilized high-resolution shallow seismic data acquired during a post-earthquake cruise to find evidence of gas seeps, gas-charged sediments, and sediment failure in the Eastern (Izmit) Basin of the Gulf of Izmit. The data showed anomalies that suggest the presence of increased gas in the gulf after the earthquake. Five major zones of offshore mass movement were found in the study area. Comparison of data collected before and after the earthquake indicates that the apparent amount of gas increased after the earthquake and the mass movement has a causative relationship to the August 17, 1999 earthquake. Therefore, we conclude that the seismic event, presence of increased gas, and the offshore mass movements in the study area are interrelated. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Gulf of Izmit; North Anatolian Fault; 1999 Izmit earthquake; high-resolution shallow seismic study; gas-charged sediments; seafloor gas seep; offshore mass movement; DEBRIS FLOWS; HYDROCARBON GASES; CONTINENTAL-SHELF; ACTIVE FAULTS; POCKMARKS; CALIFORNIA; OFFSHORE; SLOPE; SUBMARINE; Geology; Oceanography